Peningkatan Efektifitas Pancing Ulur Kakintu Kindaeng di Desa Palahanaeng Kecamatan Tabukan Tengah, Sangihe, Sulawesi Utara - Costantein Imanuel Sarapil; Eunike Irene Kumaseh; Joneidi Tamarol; Ganjar Ndaru Ikhtiagung (Politeknik Negeri Cilacap, 2024)
The problem with the fishermen group in Palahanaeng Village is the minimum number of fishing gear and the ineffectiveness of the fishing gear. This PMUP program provides education about the handline fishing gear or “Kakintu Kindaeng” fishing line, as well as counseling on the effectiveness of its use for fishermen groups. The service method that will be carried out is providing counseling and training, mentoring, and monitoring and evaluation for fishing fishermen groups in Palahanaeng Village. This community service helps fishermen groups in Palahaneng Village to increase catches, which has implications for increasing fishermen's income. Kakintu kindaeng is a common fishing gear used by fishermen in Palahanaeng Village. Kindaeng is the name of the local people for mackarel tuna fish, which is a type of pelagic fish that has economic value. The operation process is stretched out into the water by being pulled and jerked while the boat is being run using the engine. Some of these catches are sold and some are used for daily family consumption needs.